Structural topology optimization of tall buildings for dynamic seismic excitation using modal decomposition. (1st August 2020) - Martin, Amory; Deierlein, Gregory G.
Highlights: Dynamic topology optimization methods are reviewed and contrasted A novel topology optimization formulation is introduced to tackle seismic loading. The lateral bracing systems of tall buildings is investigated using both 2D and 3D examples. The impact of earthquake characteristics on the optimized geometry of buildings is discussed. Abstract: Structural topology optimization has been successfully investigated to improve the designs of a variety of civil, mechanical and aerospace applications. While topology optimization for static loading is fairly well developed, methods for dynamic seismic loading remain a challenge. In this paper, dynamic topology optimization methods are reviewed and contrasted, focusing on frequency domain techniques. Inspired by earthquake engineering analysis methods, a dynamic topology optimization formulation called the sum of modal compliances (SMC) is proposed. By considering multiple eigenmodes, the structural vibration is minimized for a seismic excitation, described by a response spectrum. The formulation handles design-dependent loading, due to inertial effects, by performing a series of design-independent topology optimization problems, between which, the seismic modal load vector is updated. Applications for the lateral bracing of high-rise buildings on 2D and 3D examples demonstrate the capabilities of the procedure and conceptual understanding of optimization for seismic loading. Results demonstrate that the optimized topology is influenced by the earthquake frequency content, which is dependent on the soil and seismological effects beneath the structure.